Injuries in skating and sledding winter sports: patterns and imaging findings - Rizk, B.; Brat, H.; Pirrello, T. (Seminars in Muscoloskeletal Radiology, 2022)
While skiing and snowboarding are amongst the most common winter sports, skating and sledding activities are also popular for competition or recreation. Related injuries following an acute trauma mainly involve head, spine, upper and lower limbs. For elite athletes, overuse injuries represent a significant burden. In skating, lesions can be related to boot structure and design. This article reviews epidemiology, patterns, and imaging findings of common injuries in ice skating, short track speed skating, curling, luge, bobsleigh, and skeleton.